CORRUPTION PREVENTION AND CONTROLS - INP Budiartha (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
This paper entitled corruption prevention and controls that aims to examine the factors causing corruption; control and prevention strategy of corruption. The study was conducted by a normative approach and the concept of law through the analysis of legal interpretation. The results showed that there were four aspects of the factors causing corruption in Indonesia, namely: 1) individual behavior aspect, 2) organization, 3) society aspect and 4) legislation aspect. The strategy of corruption prevention and controls can be done through: 1) the preventive action that is to prevent corruption by eliminating or minimizing the causative factors / opportunities of corruption; 2) the detective action that is instrument to support the prevention of corruption through internal supervision by the relevant government agencies and external supervision through CPC, DPR/DPRD, NGOs and communities; 3) the repressive action by means of curbing or processing those committed corruption in accordance with the legislation without exception or it is done indiscriminately. Keywords: Control, Prevention, Corruption.